Pelatihan Video Pembelajaran Kreatif di Era New Normal bagi Guru PAUD di Kecamatan Tanjung Bintang, Lampung Selatan - Laila Nursafitri; Elly Purwanti; Fitriyah Fitriyah (University of Merdeka Malang, 2021)
Online learning was chosen as the main alternative in implementing learn from home during a pandemic. There are many media that can be used in online learning such as learning videos. Learning videos are a medium for early childhood when they learn from home. Learning videos have components that make it easier for children to learn. Therefore, early childhood education (PAUD) teachers independently should be able to develop learning media. Thus, they can keep assisting students in learning both direct or long distance. This program aims to improve the skills of creative learning videos develop for PAUD teachers. This program collaborates with 3 institutions: PAUD Rumah Balita Pintar, TK Rumah Balita Pintar, and PAUD Setia Bunda in Tanjung Bintang. The program consists of introducing learning videos, training on video applications, and assisting in developing creative learning videos for early childhood. Hopefully with this activity PAUD teachers in Tanjung Bintang are able to developing creative learning videos for early childhood.DOI: https://doi.org/10.26905/abdimas.v6i1.4919